2009
DOI: 10.1155/2010/465162
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Primary Endometrioid Carcinoma of the Ovary and Synchronous Malignancy of the Endometrium

Abstract: Objective. Ovarian and endometrial cancers coincide rather frequently in the same patient. Few data are available on the involvement of the specific morphological subtypes. To identify histological pathways in the synchronous occurrence, a population-based study was performed in The Netherlands. Methods. Using the national pathology database (PALGA) information of ovarian cancers and of earlier or later cancer in the endometrium was obtained. 5366 Patients were identified with primary malignant epithelial or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
(29 reference statements)
2
27
0
Order By: Relevance
“…Yuantaoliu et al reported 43 cases of synchronous tumours of which 30% showed dissimilar histology [7] .There are only a few reports of synchronous endometrial carcinoma with an ovarian carcinoma of mucinous morphology. Catharina et al reported 53 cases of synchronous endometrial and ovarian tumours of which 75% were endometrioid carcinomas 8 . They reported 7 cases of ovarian mucinous carcinomas with endometrioid endometrial carcinomas in their study .Sylwia et al reported 10 cases of which 1 was ovarian mucinous carcinoma with endometrioid endometrial carcinoma [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Yuantaoliu et al reported 43 cases of synchronous tumours of which 30% showed dissimilar histology [7] .There are only a few reports of synchronous endometrial carcinoma with an ovarian carcinoma of mucinous morphology. Catharina et al reported 53 cases of synchronous endometrial and ovarian tumours of which 75% were endometrioid carcinomas 8 . They reported 7 cases of ovarian mucinous carcinomas with endometrioid endometrial carcinomas in their study .Sylwia et al reported 10 cases of which 1 was ovarian mucinous carcinoma with endometrioid endometrial carcinoma [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the oncogenic stimuli, synchronous development of same form of epithelial tumors in the endometrium and ovaries is not a rare event [6][7][8]. Hyperestrogenic status plays an essential part in the origin of endometrioid adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the oncogenic stimuli is, synchronous development of the same form of epithelial tumors in the ovary and endometrium is not a rare event [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…9 For instance, population studies including women with ovarian cancer have reported an incidence of less than 3%, while analyses of first-stage endometrial carcinoma have reported an incidence of STOUs of 0.31% . [10][11][12] Zaino et al have claimed that the incidence of STOUs in women with ovarian cancer is 10% and no more than 5% in women with endometrial cancer, while Irving has reported an incidence of 15-20%. 13,14 This inconsistency is associated with the different characteristics of the analysed populations, sample size, more organised prevention methods and more precise diagnostics.…”
Section: Discussionmentioning
confidence: 99%